Pengaruh Model Pembelajaran Project Based Learning, Motivasi Belajar Terhadap Hasil Belajar Mata Pelajaran Geografi - Otrin Nabang; Vitus No; Laurens Kaluge; Endah Andayani (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2021)
The purpose of this research is to explain early learning capabilities, characteristics, learning models whether peer-driven motivation affects learning outcomes. The approach used in this study is quantitative, the data obtained during the study of trainee value analyses prior to treatment and trainee value analyses after treatment. Based on the results of dummy data analysis of the significant value of the motivation to learn from pre test is 0.051 and post test is 0.067 indicates that 0.051 would indicate that any impulse effect of learning from an experiment class as well asa class of control to test the original pre test abilities and class control. For the test of the t- test the motivation effect on study results is 0,000< 05, then it is estimated that there is a significant amount of motivation for learning results.